Advances in insect physiology - Beament, James, 1921-2005; Treherne, J. E.; Wigglesworth, Vincent B. (Vincent Brian), Sir, 1899-1994 (Advances in insect physiology ;, 1967)
ADVANCES IN INSECT PHYSIOLOGY VOL 4 APL.